Synthesis and Biological Evaluation of New Phthalazinone Derivatives as Anti‐Inflammatory and Anti‐Proliferative Agents. Issue 2 (3rd January 2016) - Hameed, Alhamzah Dh.; Ovais, Syed; Yaseen, Raed; Rathore, Pooja; Samim, Mohammed; Singh, Surender; Sharma, Kalicharan; Akhtar, Mymona; Javed, Kalim
Abstract : The chemistry of phthalazine derivatives has been of increasing interest since many of these compounds have found many chemotherapeutic applications. So this study aims to synthesize a library of phthalazine derivatives and to investigate their anti‐inflammatory and anti‐proliferative activities. Sixteen new phthalazinone derivatives (2a–p ) were synthesized and tested for their in vitro antiproliferative and in vivo anti‐inflammatory activities. All the synthesized compounds were identified and characterized by IR, 1 H NMR, 13 C NMR spectroscopy, and MS. Two compounds, 2b and2i, showed significant anti‐inflammatory activity comparable with that of the standard drug etoricoxib in the carrageenan‐induced rat paw edema model at 3 and 5 h, respectively. Three compounds (2h, 2j, and2g ) showed moderate sensitivity toward the renal cancer cell line UO‐31. Abstract : A library of new phthalazone compounds (2a –p ) was synthesized as dual inhibitors (COX‐2/LOX‐5) and evaluated for their anti‐inflammatory, anticancer activities. Two compounds showed significant anti‐inflammatory activity comparable with that of the standard drug etoricoxib, whereas three compounds showed moderate sensitivity toward the renal cancer cell line UO‐31.